Cartografías de la nación sudafricana: colonialismo, apartheid y prácticas visuales en insurgencia - Arce Padrón, Yissel (El Colegio de México, 2014)
This text addresses the intersection between art, society and power in South Africa under apartheid. The study focuses on racial segregation in art, where black expressions were minimized and the black population was denied art education. To this end, an analysis is made of some of the visual works of artists Penny Siopis and Sue Williamson, white artists who, through their creations, challenged official history and made known the experiences of black women. Key works such as Patience on A Monument and A Few South Africans allow us to see how the artists rescued female agency, endowing the domestic space with a political dimension and resistance.